Conteúdo material do equilíbrio econômico financeiro de contratos de concessão - Canever, Henrique Nunes (2016)
The dissertation assumes that the initial establishment of the economic and financial balance in the concession agreements have to use theories, concepts and methodologies of other sciences that not only the legal sciences, particularly the economic and financial sciences. In this sense, the dissertation identifies the applicable methodologies to define the substantive content of the initial economic and financial equation and the different ways of quantifying the effects of the occurrence of risks in changing the original economic-financial balance of the concession contracts.